Same kind of different as me [videorecording (DVD)] - Carney, Michael (Filmmaker); Kinnear, Greg, 1963-; Zellweger, Renée, 1969-; Hounsou, Djimon, 1964-; Voight, Jon, 1938-; Hall, Ron, 1945- (Paramount Home Entertainment, 2018)
International art dealer Ron Hall must befriend a dangerous homeless man in order to save his struggling marriage to Deborah, a woman whose dreams will lead all three of them on the journey of their lives.